THE DIGITAL SKILLS OF SCHOOL ADMINISTRATORS UNDER THE PRIMARY EDUCATION SERVICE AREA KHON-KAEN 4 - Dongruangsri, Matinee; PHRAKHRUDHAMMABHISAMAI (Journal of Humanities and Social Sciences Mahamakut Buddhist University Isan Campus, 2024)
The purposes of this research were 1) to study The Digital skills of school administrators under the primary education service area Khon-Kaen 4,2) to compare The Digital skills of school administrators under the primary education service area Khon-Kaen 4, is classified by gender, educational qualifications, and work experience. The target group was 176 school administrators. The research tools include questionnaires. Statistics used in data analysis were frequency, percentage, mean, standard deviation, t-test, and one-way analysis of variance. The research results showed that 1) The Digital skills of school administrators under the primary education service area Khon-Kaen 4, the overall average was equal to 4.30. When considering each aspect, it found that analytical thinking skills in the use of digital by school administrators (average equal to 4.43), human resource management skills in digital organizations (average equal to 4.30), and digital problem-solving skills and laws in digital literacy (average equal to 4.30)and information technology development skills (average equal to 4.25) and knowledge management skills and experiences to manage digital organizations (average equal to 4.24) and skills in evaluating digital organization operations. (The average is 4.20) 2) Results of comparing The Digital skills of school administrators under the primary education service area Khon-Kaen 4,with different genders, different educational levels, and different work experiences. There are no various opinions. Statistically significant at the 0.05 level.